Draft Annual Plan (2010-2011) Part-III (Statements) Government of Tripura - Planning Commission (Planning Commission, 2010)
Agri and Allied Activities, Rural Development, Special Area Programme, Irrigation and Flood Control, Energy, Industry and Minerals, Transport, Communications, Science, Technology and Environment, General Economic Services.
Planning (P and C) Department, Government of Tripura
Planning (P and C) Department, Government of Tripura